2003
DOI: 10.1099/ijs.0.02583-0
|View full text |Cite
|
Sign up to set email alerts
|

Flavobacterium gelidilacus sp. nov., isolated from microbial mats in Antarctic lakes

Abstract: Twenty-two isolates from microbial mats in eastern Antarctic lakes showed similar fatty acid compositions and were investigated further using a polyphasic taxonomic approach. Repetitive extragenic palindromic DNA-PCR fingerprinting of the 22 strains revealed three groups, and DNA-DNA hybridizations between representatives showed more than 87 % DNA-DNA reassociation with each other. 16S rRNA gene sequence analysis placed two representative strains, LMG 21477 T and LMG 21619, within the genus Flavobacterium, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
60
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 18 publications
6
60
0
Order By: Relevance
“…Members of the phylum Bacteroidetes are abundant in freshwater and marine ecosystems and these bacteria may have a specialized role in the uptake and degradation of organic matter in cold, aquatic environments (Kirchman, 2002). Several novel species, added to the genus Flavobacterium since 1996, have originated from Antarctic habitats (Van Trappen et al, 2003, 2004; and references cited therein).During the MICROMAT project (November 1998-February 2001, 746 bacterial strains were isolated under heterotrophic conditions from microbial mat samples that were collected from ten Antarctic lakes (Van Trappen et al, 2002). Numerical analysis of the fatty acid composition of the isolates and 16S rRNA gene sequence analysis, performed on representative strains, showed that the diversity of heterotrophic bacteria in microbial mats from Antarctic lakes is very high.…”
mentioning
confidence: 99%
“…Members of the phylum Bacteroidetes are abundant in freshwater and marine ecosystems and these bacteria may have a specialized role in the uptake and degradation of organic matter in cold, aquatic environments (Kirchman, 2002). Several novel species, added to the genus Flavobacterium since 1996, have originated from Antarctic habitats (Van Trappen et al, 2003, 2004; and references cited therein).During the MICROMAT project (November 1998-February 2001, 746 bacterial strains were isolated under heterotrophic conditions from microbial mat samples that were collected from ten Antarctic lakes (Van Trappen et al, 2002). Numerical analysis of the fatty acid composition of the isolates and 16S rRNA gene sequence analysis, performed on representative strains, showed that the diversity of heterotrophic bacteria in microbial mats from Antarctic lakes is very high.…”
mentioning
confidence: 99%
“…Flavobacterium species are physiologically diverse: they can be psychrophilic, psychrotolerant or mesophilic, and can be halophilic, halotolerant or sensitive to salts. As a reflection of their physiological diversity, Flavobacterium species have been isolated from various habitats such as freshwater sediments and soil (Bernardet et al, 1996;Tamaki et al, 2003;McCammon & Bowman, 2000), a glacier (Zhu et al, 2003) and Antarctic lakes (Van Trappen et al, 2003, 2004McCammon et al, 1998;McCammon & Bowman, 2000;Humphry et al, 2001;Yi et al, 2005).…”
mentioning
confidence: 99%
“…The G+C content of DNA from the Antarctic strains was determined using an HPLC method, as described by Van Trappen et al (2003). The G+C contents of strains LMG 21470 T , LMG 21966 and LMG 21965 were respectively 37?8, 38?7 and 38?9 mol%.…”
mentioning
confidence: 99%
“…Morphological, physiological and biochemical tests were performed, as described previously (Van Trappen et al, 2003). The strains show the typical morphological characteristics of members of the Flavobacteriaceae (Bernardet et al, 2002) and their physiological and biochemical characteristics are given in the species description.…”
mentioning
confidence: 99%